2008
DOI: 10.1002/anie.200704136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Radical Cation of an NADH Analogue in Two‐Electron Reduction of a Protonated p‐Quinone Derivative by an NADH Analogue

Abstract: An electron‐transfer pathway is preferred to a direct hydride‐transfer pathway in two‐electron reduction of protonated 1‐(p‐tolylsulfinyl)‐2,5‐benzoquinone by the NADH analogue 10‐methyl‐9,10‐dihydroacridine, as has been demonstrated for the first time by ESR detection of the resulting radical cation of the acridine derivative (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…In this context, it is important to consider that extensive fundamental investigations of the mechanism of NAD(P)H oxidation have demonstrated that hydride transfer can also occur in a stepwise manner by sequential electron-proton-electron transfer (35-44) (Equation 1). These investigations documented the formation of radical cations and radicals ofNAD(normalP)H+ANAD(normalP)normalH+normalANAD(P)AH+NAD(P)++HANAD(P)H and its analogues, which have been characterized with the aid of electronic absorption and EPR spectroscopic methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to consider that extensive fundamental investigations of the mechanism of NAD(P)H oxidation have demonstrated that hydride transfer can also occur in a stepwise manner by sequential electron-proton-electron transfer (35-44) (Equation 1). These investigations documented the formation of radical cations and radicals ofNAD(normalP)H+ANAD(normalP)normalH+normalANAD(P)AH+NAD(P)++HANAD(P)H and its analogues, which have been characterized with the aid of electronic absorption and EPR spectroscopic methods.…”
Section: Resultsmentioning
confidence: 99%
“…The formation and detection of these reactive species indicated that the oxidation of NAD(P)H and its analogues can occur stepwise via electron-proton-electron transfer of hydride, if the acceptor is also capable of undergoing a stepwise two electron reduction. This point has been recently underscored with the EPR and electronic absorption spectroscopic detection of a radical cation of an NADH analogue in the thermal two-electron reduction of a quinone (35). Moreover, it has also been demonstrated that in the absence of H 2 O 2 , the oxidation of NADH by native horseradish peroxidase (HRP) begins with single-electron transfer from NADH to ferric HRP to form the NADH •+ radical cation and ferrous peroxidase (39).…”
Section: Resultsmentioning
confidence: 99%
“…þ is observed in the HisÁ2H þ -promoted hydride transfer from AcrH 2 to TolSQ. 81 The stoichiometry was confirmed by the spectral titration of TolSQ by AcrH 2 in the presence of HClO 4 (Figure 2.11a), where all TolSQ molecules are consumed by addition of 1 equivalent of AcrH 2 to yield 1 equivalent of AcrH þ . 49 2.4.1.2 Stepwise Electron Transfer Pathway A more efficient reduction of TolSQ by AcrH 2 occurs to yield AcrH þ and TolSQH 2 in the presence of perchloric acid (HClO 4 ), whereas no reaction occurs between AcrH 2 and TolSQ in the absence of HClO 4 .…”
Section: ð2:2þmentioning
confidence: 87%
“…49 2.4.1.2 Stepwise Electron Transfer Pathway A more efficient reduction of TolSQ by AcrH 2 occurs to yield AcrH þ and TolSQH 2 in the presence of perchloric acid (HClO 4 ), whereas no reaction occurs between AcrH 2 and TolSQ in the absence of HClO 4 . 81 The dynamics of the reduction of TolSQ by AcrH 2 in the presence of HClO 4 monitored by using a stopped-flow technique revealed the formation of ET intermediate as shown by a transient absorption band at l max ¼ 640 nm (Figure 2.11b), which is ascribed to AcrH 2 . 81 The promoting effect of HClO 4 on the reduction of TolSQ by AcrH 2 should result from protonation of TolSQ (TolSQ þ H þ !…”
Section: ð2:2þmentioning
confidence: 99%
See 1 more Smart Citation